2016
DOI: 10.1002/elsc.201600169
|View full text |Cite
|
Sign up to set email alerts
|

Bioscrubber treatment of exhaust air from intensive pig production: Case study in northern Germany at mild climate condition

Abstract: Treatment by field‐scale bioscrubber of exhaust air, including ammonia (NH3) and the greenhouse gases methane (CH4), nitrous oxide (N2O), and carbon dioxide (CO2), from 13 intensive pig production houses located in northern Germany were investigated in 2013 and 2015. NH3 removal efficiencies varied between 35 and 100% with an overall average value of 79% under the NH3 inlet fluctuations from 34 to 755 g d−1 m−3 in both 2013 and 2015. Results of the electron microscopic analyses demonstrated that the bacteria N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
2
10
0
4
Order By: Relevance
“…The significant difference between the relationships proposed by Melse et al (2012) and Liu et al (2017) may be due to differences in the water they analyzed, the relationship proposed by [19] being obtained for only one pig farm. Nonetheless, the slope obtained by [17] was 53% greater than the theoretical value (on the basis of the slope: i.e., 0.3 vs. 0.196) and the intercept (+5.48 mS cm −1 ) seems unrealistic. A similar finding was also reported by Van der Heyden et al [18] for a pig fattening facility located in Belgium: L −1 as the unit for ammonium and considering that ammonium concentration is balanced by nitrite and nitrate concentrations, the slope is therefore 2 × 123.75/1000 = 0.247, i.e., 26% higher than the theoretical value.…”
Section: Rationalementioning
confidence: 69%
See 3 more Smart Citations
“…The significant difference between the relationships proposed by Melse et al (2012) and Liu et al (2017) may be due to differences in the water they analyzed, the relationship proposed by [19] being obtained for only one pig farm. Nonetheless, the slope obtained by [17] was 53% greater than the theoretical value (on the basis of the slope: i.e., 0.3 vs. 0.196) and the intercept (+5.48 mS cm −1 ) seems unrealistic. A similar finding was also reported by Van der Heyden et al [18] for a pig fattening facility located in Belgium: L −1 as the unit for ammonium and considering that ammonium concentration is balanced by nitrite and nitrate concentrations, the slope is therefore 2 × 123.75/1000 = 0.247, i.e., 26% higher than the theoretical value.…”
Section: Rationalementioning
confidence: 69%
“…Note that typical values for ground water would be lower than 1 mS cm −1 , but higher values are possible [22,23]. Another linear regression was proposed by Liu et al [17] in a study dedicated to 13 field-scale bioscrubbers in northern Germany. These authors reported the following relationship: EC mS/cm = 3.34Σ ([NH 4…”
Section: Rationalementioning
confidence: 98%
See 2 more Smart Citations
“…Existing microclimate systems on farms in their physical buildup do not have air purification and recuperation devices [1, 5,11,13,16,17,18,20,23].…”
Section: Optimization Of the Technological Regimes Of The Microclimatmentioning
confidence: 99%